2022
DOI: 10.31223/x5b06s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heralds of a Future Eruption? Swarms of Microseismicity beneath the submarine Kolumbo Volcano indicate Opening of near-vertical Fractures exploited by ascending Melts

Abstract: The Kolumbo submarine volcano in the southern Aegean (Greece) is associated with repeated seismic unrest since at least two decades and the causes of this unrest are still hardly understood. We present a ten-month long microseismicity dataset for the period 2006-2007. The majority of earthquakes clusters in a cone-shaped portion of the crust below Kolumbo. The tip of this cone coincides with a low Vp-anomaly at 2-4 km depth, that is interpreted as a crustal melt reservoir. Our dataset includes several earthqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 65 publications
0
8
1
Order By: Relevance
“…The earthquakes were clustered in several swarms starting with the strongest events at 6-9 depth and migrating upwards, terminating at the base of the LVZ. The swarm propagation was faster than expected for hydrothermal gases diffusing from a point source or for active diking (Schmid et al, 2022). However, the speed and focal mechanisms associated with the swarms remain consistent with melt ascent along pre-existing, subvertical pathways through a rheologically strong layer at 4-9 km b.s.l.…”
Section: Relationship With Seismic Activitymentioning
confidence: 57%
See 4 more Smart Citations
“…The earthquakes were clustered in several swarms starting with the strongest events at 6-9 depth and migrating upwards, terminating at the base of the LVZ. The swarm propagation was faster than expected for hydrothermal gases diffusing from a point source or for active diking (Schmid et al, 2022). However, the speed and focal mechanisms associated with the swarms remain consistent with melt ascent along pre-existing, subvertical pathways through a rheologically strong layer at 4-9 km b.s.l.…”
Section: Relationship With Seismic Activitymentioning
confidence: 57%
“…A recent seismicity study by Schmid et al (2022) shows that the observed anomaly coincides with the tip of a cone-shaped region hosting enhanced seismic activity in the 2006-2007 period. The earthquakes were clustered in several swarms starting with the strongest events at 6-9 depth and migrating upwards, terminating at the base of the LVZ.…”
Section: Relationship With Seismic Activitymentioning
confidence: 81%
See 3 more Smart Citations